The Influence of Service Standards and Work Culture on Customer Satisfaction through Employee Performance : (Case Study on Public Services Recognition of Information Security Consulting Institutions and Certification Institutions at BSSN) - Achmad, Fadly; Riau, Dwi Putranto; Akadira, Tora (Yayasan Ilomata, 2025)
This study examines the impact of service standards and work culture on customer satisfaction through employee performance in recognition of Information Security Consulting Institutions and Certification Institutions service at BSSN. The novelty of this research lies in the composition of variables and models used. Previous studies have analyzed the relationship between service standards, work culture, and customer satisfaction, indicating that both factors positively influence customer satisfaction and employee performance. However, no similar research has been conducted at BSSN, making this study valuable for policy improvements to enhance customer satisfaction through better service standards and provider performance. This research employs a quantitative method using primary data collected from questionnaires distributed to 70 respondents who use BSSN services. Data analysis uses variance-based SEM (PLS) with SMART PLS 3.0. The findings reveal that service standards, work culture, and employee performance positively influence customer satisfaction. All hypotheses are accepted, confirming that service standards and work culture, both individually and simultaneously, positively impact employee performance and customer satisfaction.